SYSTEM-FORMING OBJECTS OF THE SACRED SPHERE OF THE IVAN-FRANKIV REGION - Хіміч, Марія (SWorldJournal, 2023)
The article examines scientific approaches to determining the origin of objects of the sacred sphere, which act as system-creating objects, "cores" or "centers" in the formation of the structure of the sacred sphere. The diversity of natural, natural-anth